Smart Nanotheranostics Responsive to Pathological Stimuli - Parodi, Alessandro; Rudzinska, Magdalena; Leporatti, Stefano; Anissimov, Yuri; Zamyatnin, Andrey A. (Frontiers in Bioengineering and Biotechnology, 2020)
The development of nanotheranostics represents one of the most dynamic technological frontiers in the treatment of different pathological conditions. With the goal in mind to generate nanocarriers with both therapeutic and diagnostic properties, current research is focused on implementing these technologies with multiple functions, including targeting, multimodal imaging, and synergistic therapies. The working mechanism that stands at the base of nanotheranostics can rely on physical, chemical, and biological triggers that allow for the activation of the theranostics properties only at the diseased site. In this review, we explored new advances in the development of smart nanotheranostics responsive to pathological stimuli, including altered pH, oxidative stress, enzymatic expression, and reactive biological molecules with a deep focus on the material used in the field to generate the particles and their working mechanism.